SIKAP MASYARAKAT NELAYAN KAMPUNG BIDUK-BIDUK TERHADAP IMPLEMENTASI PROGRAM KAWASAN KONSERVASI PERAIRAN PESISIR DAN PULAU-PULAU KECIL (KKP3K) KEPULAUAN DERAWAN DAN PERAIRAN SEKITARNYA DI KABUPATEN BERAU PROPINSI KALIAMANTAN TIMUR - Hendra Wahyu Luchyto; Erwiantono; Dayang Diah Fidhiani (Jurnal Pembangunan Perikanan dan Agribisnis, 2019)
The purpose of this research is to determine the characteristics of the social economy, perception, motivation, and the general attitude towards the coastal area development programme. Also to know the relationship between socio-economic characteristics, perceptions and motivations with the general attitude of the fishing communities in Biduk-Biduk toward program implementation the implementation of the conservation area. Data retrieval method using the technique of random proportional sampling with 74 respondents. Research conducted for 9 months starting from June 2018 up to February 2019. Methods of data analysis using the method of qualitative and quantitative methods of analysis a descriptive statistical tests Spearman Rank correlations. Factors socioeconomic characteristics related to the attitude of the fishing communities in Biduk-Biduk toward program implementation conservation area, on the variables of age and work experience. Factors related to the perception of attitude variables contained on the concept of suitability and intensity of extension officers. Motivation factors that there is a relationship to an attitude that is variable the desire to preserve marine resources, fisheries-towards the implementation of the program of conservation areas.